2015
DOI: 10.1016/j.apm.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the supply chain structure on bullwhip effect

Abstract: Please cite this article as: R. Dominguez, S. Cannella, J.M. Framinan, The impact of the supply chain structure on bullwhip effect, Appl. Math. Modelling (2015), doi: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 121 publications
0
31
0
1
Order By: Relevance
“…Li et al (2014) study the bullwhip behavior when the Damped Trend forecasting method is applied with the order-up-to replenishment policy, and identify the sufficient conditions under which the bullwhip effect will be generated as well as the necessary conditions under which the bullwhip effect may be avoided. Dominguez et al (2015) analyze the impact of the supply chain structure on the bullwhip effect. Their results show that facing a stable demand, the number of echelons is the dominant factor influencing the bullwhip effect; however, under a sudden shock in market demand, increasing the number of nodes and the divergence of the supply chain will increase the bullwhip effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2014) study the bullwhip behavior when the Damped Trend forecasting method is applied with the order-up-to replenishment policy, and identify the sufficient conditions under which the bullwhip effect will be generated as well as the necessary conditions under which the bullwhip effect may be avoided. Dominguez et al (2015) analyze the impact of the supply chain structure on the bullwhip effect. Their results show that facing a stable demand, the number of echelons is the dominant factor influencing the bullwhip effect; however, under a sudden shock in market demand, increasing the number of nodes and the divergence of the supply chain will increase the bullwhip effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The values of all parameters are restricted by Equation (18), and the stable region with respect to the price adjustment speed can also be determined by the above conditions. In this paper, we are interested in the complexity of system (7) affected by parameters α and β.…”
Section: Proof (See Appendix A)mentioning
confidence: 99%
“…Dominguez et al [17,18] found that the bullwhip can be considerably reduced by collaboration or the smoothing replenishment rules in divergent supply chain networks.…”
Section: Introductionmentioning
confidence: 99%
“…A common phenomenon shown by Supply Chain Networks (SCNs) is the so-called bullwhip effect [1], which refers to an increase of the variability of order in the upstream direction toward producers and suppliers [2]. SCN managers and researchers have paid a lot of attention on this phenomenon due to its importance in nowadays economy, [3,4].…”
Section: Introductionmentioning
confidence: 99%